From real – time manufacturing to IoT digital technologies - Ciortea, Elisabeta Mihaela (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The paper deals with several aspects of Petri networks, their implications in the modeling, analysis, synthesis and implementation of systems in the field of manufacturing. Since these aspects are being analyzed based on discrete events systems and because everything is done in real time, it is recommended that digital technology is accessed using IoT devices. For the chosen manufacturing system, we will only model and analyze the sectors in which the importance of the component systems can be highlighted in real time. Even though Petri networks are no longer secret in use, they are easy to use in simulation and modeling, and the resulting diagrams are easy to interpret. The synthesis and implementation proposed in this paper are considered cloud-based because the security of information is much more complex. The tracking and control system is proposed to be managed using IoT systems and all levels to provide the most accurate security of the manufacturing process. This system can be used in enterprises that adopt the implementation of IoT systems, implement digital technology. The system can only be applied to manufacturing sectors, and should not cover the whole system from supply to disposal.